ผลของการเสริมวิตามินอีในอาหารปลาดุกอุยต่อคุณภาพน้ำเชื้อ - สมนึก เถลิงเกียรติ; สมนึก ณัฏฐวรรณ; เสาวกูล สำเนาว์; เสาวกูล กฤติมา (วารสารเกษตรพระจอมเกล้า, 2019)
This research aimed at determining the amount of vitamin E and sperm stimulate time to increase semen quality of broad head catfish to hatchery. Randomize complete block design was designed for the experiment, using male catfish with the average weight of 80 ± 1.03 g and the average length of 18 ± 1.90 cm Fish raised with three different levels of vitamin E (0, 600 and 1,000 mg kg-1) was divided into 3 groups (200 fish each) with 3 replicates. Twenty of fish per group was randomly collected every 15 days for 90 days. Subsequently, first 10 fish was collected sperm sac and evaluated for sperm quality and other ten fish was used to stimulate sperm before artificial breeding method with 5 different time courses (0 1 2 3 and 4 min). The study indicated that sperm motility was statistically different (p <0.05). It was found that vitamin E supplement at the level of 1,000 mg had the highest average motion (85.00 ± 6.24%). Vitamin E supplement at the level of 600 mg kg-1 contributed the highest viability and sperm concentration at 68.28±3.42% and 51.02±3.58 x 106 cells/ml, respectively. Fertilization rate and hatching rate obtained from 600 mg kg-1 vitamin E and 2-min stimulation were 92.50 ± 3.35% and 79.50 ± 0.70%, respectively. Therefore, supplementation of vitamin E in diet at 600 mg kg-1 with 2-min sperm stimulation with freshwater before the artificial breeding of catfish, could enhance the hatching rate of broad head catfish.0.3